Olanzapine as a Cause of Urinary Incontinence: A Case Report - Mobolaji Usman Dada; Lateef Olutoyin Oluwole; Patrick T Adegun; Peter O Tareo (Iranian Journal of Psychiatry, 2012)
Olanzapine, an atypical antipsychotic, is one of the most commonly used antipsychotics. Though olanzapine is commonly associated with endocrine side effects, it is generally well tolerated by most patients and is rarely associated with urinary incontinence. This report highlights the case of a 23 -year old male patient with schizophrenia who developed severe urinary incontinence following the use of olanzapine. No medications were given to relieve the incontinence contrary to some other studies where ephedrine was used. Olanzapine was changed to trifluoperazine, and the patient's condition improved within two days. Urinary incontinence, though uncommon, is an embarrassing side effect of olanzapine which could negatively affect drug compliance. As such, clinicians should enquire about it in order to improve the patient’s health.